University Accounting Programs in Canada: Inventory and Analysis (Book). - Meyer, Philip E.; Mitchell, C. L. (The Accounting Review, 1982)
Abstract Reviews the book "University Accounting Programs in Canada: Inventory and Analysis," by Thomas H. Beechy.